Anthropological characteristics and biological age in soccer players - Erceg, M.; Miletic, A.; Rana, A.; Jelaska, I. (3rd International Scientific Conference: Exercise and quality of life. April 12/13th 2013, 2013)
In order to determine the differences between individual morphological characteristics and motor abilities of 45 U14 soccer players (although all of different biological age), an experiment was conducted with a battery of 10 morphological and 11 motor skills tests. The subjects were divided into two age groups: a younger, pre-U14 age group and the U14 player group. Biological maturity was visually assessed using the maturity stages classification according to the Tanner test. Based on the assessment of biological maturity, the subjects were divided into three groups (pre-puberty, early puberty and mid-puberty). The differences between motor and morphological characteristics of U14 soccer players of different biological age were analyzed using a one-way ANOVA and Fischer LSD post hoc test. Significant differences were found between the subjects of same chronological age, but different biological age, especially in morphology. These results suggest that biological age significantly affects morphological characteristics, which was to be expected considering the age and the sensitive life stage. Maturation has less effect on motor skills because it doesn't depend on biological age as much as it is a result of training and repetition.